Managerial Competence of School Principals in Improving the Quality of Institutions - Asyari, Hasyim; Fangestu, Indra Wahyuni Firli; Al Husna, Naila Shopia (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The progress of a school depends on the competence of the leader or principal because the competence of the principal himself is one of them in the managerial realm, which is directly related to the achievement and progress of the school as an Educational Institution. Therefore, this study aims to find out how the managerial competence of school principals in improving school quality. Data collection techniques carried out are observational analysis, interviews, and documentation outlined in qualitative descriptive form. Based on the results of research data analysis from observations and interviews, conclusions were obtained, namely; The managerial competence of the principal in improving the quality of the institution at SDIT Laa Tahzan, Citra Raya Tangerang has had a good impact on the progress of the school, because the principal at the school has the maximum managerial ability and is able to apply it optimally which includes; 1) Conceptual skills, in this case the principal is able to carry out school planning and curriculum development by national education objectives, 2) Human relations skills, in this case the principal can utilize teachers and staff and build good relationships with school residents and residents around the school, 3) Technical skills), in this case, the principal can manage the resources in the school optimally, and is able to supervise and organize all forms of activities carried out. However, even though the principal has been able to manage human resources, he is still unable to manage or utilize the web-based school information system to help facilitate and support the achievement of school goals.